A pressing need to respond to the needs and sexual and reproductive health problems of adolescent girls living with HIV in low‐ and middle‐income countries. Issue 6 (1st December 2015) - Chandra‐Mouli, Venkatraman; Armstrong, Alice; Amin, Avni; Ferguson, Jane
Abstract : Introduction: This commentary provides the rationale and makes a call for greater investment and effort to meet the sexual and reproductive health (SRH) problems of adolescent girls living with HIV in low‐ and middle‐income countries (LMIC). Discussion: Adolescent girls in LMIC are at a greater risk of acquiring HIV infection than their male peers. They also face a number of other serious SRH problems – early pregnancy, pregnancy‐ and childbirth‐related complications, unsafe abortions, sexual abuse and intimate partner violence and sexually transmitted infections. While many LMIC have made notable progress in preventing HIV in children and adults and in improving the access of these population groups to HIV treatment and care, adolescents in general and adolescent girls in particular have not received the same effort and investment. Conclusions: Much more needs to be done to implement proven approaches to prevent new HIV infections in adolescent girls in LMIC and to meet the needs of those living with HIV.